Rapid, sensitive, and visual detection of mandarin fish ranavirus and infectious spleen and kidney necrosis virus using an RPA-CRISPR/Cas12a system - Lu, Zhoutao; Liang, Mincong; Li, Chuanrui; Xu, Yichun; Weng, Shaoping; He, Jianguo; Guo, Changjun (Frontiers in Microbiology, 2024)
Iridoviruses are large cytoplasmic icosahedral viruses that contain dsDNA. Among them, mandarin fish ranavirus (MRV) and infectious spleen and kidney necrosis virus (ISKNV) are particularly notable due to their high contagiousness and pathogenicity. These viruses pose a significant threat to fish aquaculture, resulting in substantial annual economic losses for the fish farming industry. Therefore, the development of novel, rapid virus detection technologies is essential for the prevention and control of ISKNV and MRV diseases. In this study, we developed a rapid, sensitive, and visual detection method for MRV and ISKNV using the recombinase polymerase amplification (RPA)−CRISPR/Cas12a system. This method can detect as low as 1 copy/μL of MRV and 0.1 copy/μL of ISKNV, demonstrating excellent specificity and reproducibility. The detection can be performed at a constant temperature of 37–39°C, eliminating the need for complex equipment. A 30-min RPA amplification followed by a 15-min CRISPR/Cas reaction is sufficient for detecting most samples. For low-concentration samples, extending the CRISPR/Cas reaction time to 60 min improves result visibility. The designed RPA reaction system is capable of performing reverse transcription of RNA, allowing for the detection of mRNA transcribed from the MCP gene of MRV and ISKNV in the sample. Furthermore, two probes were identified that can be observed without the need for excitation light. In conclusion, a field-suitable detection method for ISKNV and MRV has been established, providing a powerful tool for the prompt diagnosis of these aquatic pathogens and aiding in the prevention and control of ISKNV and MRV diseases.